WORLD WIDE WEB 3.0 UNTUK DAKWAH: MANFAAT DAN STRATEGI PENGGUNAANNYA - Nurdin Nurdin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
World wide web has been significantly improved since it was founded in 90s. Currently, we use web 3.0 or the third generation web which is a semantic and personalized web. Previous studies found that web 3.0 has been effectively used for many purposes such as business, politic, efucation, etc. Web 3.0 is considered able to imporove user experiences in fullfiling their information needs because it is more personalized and real time as well as able to underatnd user needs. Eventhough benefits of use of web 3.0 has been proved in previous studies, Muslim yet to underastand how the web 3.0 can be utilized in dakwah activities. This study, therefore, will provide insight on how web 3.0 platform can be used for dakwah purposes. Through the use secondary data analisis approach , this found that interesting and maeningful dakwah is potentially can be delivered through platform web 3.0. There are a number of strategies to maximize the use of web 3.0 for dakwah. Those includes creating social media accounts, digitalization of Islamic teaching materials and store them in cloud system storage, and personalization of dakwah materia. In conclusion, web 3.0 can be used for dakwah purposes through appropriate strategies as found in this study. Muslim individual and groups should improve their knowledge and skills in using web 3.0 for dakwah purposes. The limitation of this study is that the data was gathered form secondary sources only. Future reseach need to test through an empirical environment to increase validity.